The role of threat and efficacy in AIDS prevention - Witte, K (International quarterly of community health education, 1991)
Studies examining the role of fear, threat, and efficacy, in promoting protective-health behavior changes have yielded diverse results. These constructs were examined in a theoretically-based 3 (low, moderate, high threat) x 2 (low, high efficacy) factorial experiment promoting condom use to prevent HIV-transmission. Pre-screened sexually-active college students not involved in long-term relationships (N = 146) served as subjects. As predicted, when threat of AIDS was high and condom efficacy low, people failed to use condoms; when both threat and efficacy were high, people reported more condom use. The more fearful people were of AIDS, the more they denied its threat and the more manipulated they felt. Overall, the results indicated that threatening messages can motivate behavior change, as long as the recommended response is portrayed as effective. This study is useful for public health practitioners in that specific and practical guidelines for campaign message development are offered.